Evaluation of Antidiarrheal properties of ethanol extract of Brassica juncea in experimental animals - Muhammad, Aslam P; Pinkey, Rawal; Ramesh, C; Chaitra, G (Journal of Drug Delivery and Therapeutics, 2021)
Objective: The present study was designed to evaluate the anti-diarrheal potentials of ethanol extract of Brassica juncea in albino rats. Materials and methods: The defatted powder of whole plant of Brassica juncea subjected to extraction using ethanol in soxhlet apparatus.  The acute oral toxicity was studied for ethanol extract according to OECD guidelines 425. The antidiarrheal properties of ethanol extracts was assessed against castor oil induced diarrhea, magnesium sulfate induced diarrhea and charcoal passage test in albino wistar rats.Results: The ethanol extract of Brassica juncea has effectively reversed diarrhea. The extract at higher dose 400mg/kg shows significant reduction the number of feces against castor oil induced and MgSO4 induced diarrhea. In charcoal passage test, higher dose of ethanol extract also shown significant reduction in the distance travelled.Conclusion: The result obtained establish the efficiency of ethanol extract of Brassica juncea as antidiarrheal agentKeywords: Brassica juncea, castor oil, magnesium sulphate, charcoal passage test.